Somatostatin Receptor 2 Expression in Canine Meningioma. (January 2019) - Foiani, G.; Guelfi, G.; Chiaradia, E.; Mancini, F.; Trivelli, C.; Vitellozzi, G.; Lepri, E.; Mandara, M.T.
Summary: The neuropeptide somatostatin (SST) plays an important regulatory role in the proliferation of normal and neoplastic cells. Five subtypes of somatostatin receptors (SSTRs), SSTR1–SSTR5, have been identified in human tumours. The SSTR2 subtype is identified most commonly in meningiomas. Long half-life SST analogues are now recommended for the systemic treatment of unresectable or radiation-refractory recurrent human meningiomas. In this study, SSTR2 expression was evaluated in 46 canine meningiomas; in 21 cases this was by immunohistochemistry and in 25 cases by reverse transcriptase quantitative polymerase chain reaction (RT-qPCR). In addition, SSTR2 expression was evaluated by immunocytochemistry, western blotting and RT-qPCR on primary cell cultures prepared from two canine meningiomas. SSTR2 immunohistochemical expression was observed in 17/21 cases (81%), and SSTR2 mRNA expression was detected in 14/25 cases (56%). SSTR2 protein and gene expression were not significantly correlated with the tumour histological subtype or grade. Overall, meningothelial meningiomas showed constant and diffuse SSTR2 immunohistochemical expression and the highest SSTR2 gene expression level compared with other subtypes. A tendency for loss of SSTR2 in high-grade meningiomas was observed in both immunohistochemical and RT-qPCR studies. About 90% of cultured canine meningioma cells showed SSTR2 expression. In both of the meningioma cell cultures, SSTR2 expression was also detected by western blotting and RT-qPCR. This study demonstrates for the first time that canine meningioma expresses SSTR2 and that this expression is maintained in vitro . Our results, while preliminary, provide encouragement for further studies aimed at finding novel medical treatment strategies for canine meningioma, especially for tumours that are not surgically accessible.